Dzieje działalności przemysłowej w Stoczku Łukowskim i okolicach - Czepas, Piotr (Zeszyty Wiejskie, 2016)
The present paper focuses on the history of industrial activity in Stoczek Łukowski and surrounding areas. The territorial scope of the study is limited by the current administrative borders of the town and commune of Stoczek Łukowski, whereas chronologically, it focuses on the period from the 16th century and the first decade of the 21st century. The paper focuses on the history of industry in this area, which is presented by means of description of individual trades. The most powerful branches in and around Stoczek Łukowski included agriculture and food industries, especially milling, and the mineral industry – brickyards. Industrial facilities operated on the basis of the local natural resources. In terms of structure, these were mostly petty industry enterprises which served local inhabitants’ needs.